(untitled) (International Journal of Advanced Research in Science, Management and Technology, 2021)
The main aim of this paper is to provide security for ATM Centers by using IRIS Recognition. For the traditional ATM terminal, customer recognition systems rely only on bank cards, passwords and such identity verification methods which measures are not perfect and functions are too single. For solving the bugs of traditional ones, there is need to designs new ATM terminal recognition systems to verify the IRIS or face of the Account holder of the bank at ATM Center. The use of Biometric ATM’s based on IRIS recognition technology providing a safe and paperless banking environment. The iris recognition system completely eliminates the chances of fraud due to theft and duplicity of the ATM cards. This project will detect the iris of the user and allows the person to make transactions, by using matlab it detects the human IRIS and allows person for the transaction and sends the message automatically. Once we receive the OTP we need to enter that key and then it allows the transactions, plus when the attacker try to damage the ATM machine vibration detection sensors gets activated. A message is passed to the nearby police stations with the help of GSM modem and door will get lock. We can remotely monitor the user accounts for Authorized or unauthorized Access by using Internet of Things (IOT).